HEALTH CARE NEEDS OF ELDERLY WOMAN (Fiep Bulletin - online, 2014)
The elderly women population in Brazil is increasing as well as the new public politics and professional's challenges. The aim of this study is to understand the health needs of this population. It's a study based in referential theoretical methodological of Alfred Schütz's social phenomenology. Ten elderly women were interviewed. The speeches were recorded and six different categories were defined: 1) Comprehension about the health needs, 2) Behavior and lifestyle, 3) Perception about risk factors; 4) Care professional's perception; 5) Health expectations; 6) Expectations about professional care. It can be concluded that the medicalization and beliefs were highlighted in this study. The elderly women know their health needs, they're adept at healthy habits and healthy lifestyle and expect professional preventive care, resolvent and humanized.
Keywords: longevity; health care; humanization of care